(untitled) (International Journal of Nursing Education, 2022)
Dysmenorrhea is a common gynecological condition with painful menstrual cramps of uterineorigin. Primary Dysmenorrhea is widely prevalent, more than 70% of teenagers and 30-50% ofmenstruating women suffer from varying degree of discomfort. The primary objectives of the studywere to assess the effect of selected stretching exercises on pain level of primary dysmenorrhea. Quasiexperimental method was used and data was collected from 40 students who have suffered fromPrimary Dysmenorrhea by purposive sampling technique was used. Data was collected with the helpof VAS (Visual Analogue Scale). The result showed pain was significantly reduced after exercise onday 1, day2, day3. i.e. Day 1 shows 43.78% reduction, day 2 shows 53.92% reduction and day 3shows 80.14% reduction of pain. Significant difference of pain score on day 1 according to age beforeexercise among college student as P<0.01 i.e. as age increases pain decreases significantly. Conclusion-Selective stretching exercises were found to be effective in the level of dysmenorrhea among collegestudents. It is also proven that pain level is high on first day of menstruation than second and third.Further studies can be conducted to see effects of pain on further aspects of life like psychologicaleffects. Effectiveness of interventions can be check for the association with symptoms to have a broaderpicture.